The revolt of the Albanians from Kosovo through the eyes of the Bulgarian diplomacy - Božinov Vojin (Srpska Politička Misao)
Based on scientific literature and archival materials, the article analyzes the attitude of the Bulgarian embassy in Belgrade about the events in Kosovo since 1981. A special attention is paid to several important questions: what were the reasons that led to the rebellion of the students in Kosovo and by what methods the riots were quelled; what were the demands and goals of the demonstrators; what was the attitude of the Serbian and Yugoslav Communists towards the unrest in the autonomous region; how the complex situation in Kosovo may affect the neighboring Socialist Republic of Macedonia and what were the prospects for the Socialist Federal Republic of Yugoslavia after the adoption of the 1974 constitution.